2016
DOI: 10.1536/ihj.16-157
|View full text |Cite
|
Sign up to set email alerts
|

High Dose <i>β</i>-Blocker Therapy Triggers Additional Reverse Remodeling in Patients With Idiopathic Non-Ischemic Cardiomyopathy

Abstract: SummaryCarvedilol has established its evidence to improve prognosis and facilitate left ventricular reverse remodeling (LVRR) in heart failure patients with reduced left ventricular ejection fraction (LVEF), and many studies have supported its dose-dependency. However, there are few studies demonstrating the effect of high dose carvedilol in Japan. We enrolled 23 patients with idiopathic non-ischemic cardiomyopathy, in whom LVEF remained 45% or less despite 20 mg/ day of carvedilol therapy for > 3 months. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…In our study, target doses of BB therapy were more frequently achieved in patients whose LV function recovered, and we found a relationship between achievement of target doses of BB and freedom from the composite endpoint of all‐cause mortality and HF hospitalizations. These data are consistent with those of multiple prior studies that showed both the beneficial effects of BB therapy on reverse remodeling and CV outcomes, as well as the dose‐dependent incremental benefit of these therapies . Use of ACEIs was associated with a trend toward higher rates of LVR and greater freedom from the composite outcome of HF hospitalization and death.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, target doses of BB therapy were more frequently achieved in patients whose LV function recovered, and we found a relationship between achievement of target doses of BB and freedom from the composite endpoint of all‐cause mortality and HF hospitalizations. These data are consistent with those of multiple prior studies that showed both the beneficial effects of BB therapy on reverse remodeling and CV outcomes, as well as the dose‐dependent incremental benefit of these therapies . Use of ACEIs was associated with a trend toward higher rates of LVR and greater freedom from the composite outcome of HF hospitalization and death.…”
Section: Discussionsupporting
confidence: 88%
“…6,20) However, not only single moment BNP values but also changes in BNP over time have clinical significance. 18,21) Therefore, several studies have evaluated the correlations between ΔBNP, ΔLVEF, and cardiovascular outcomes, and a significant correlation between ΔBNP and recovery of LV systolic function after coronary bypass surgery has been reported. 12) In patients with mitral regurgitation, there was a significant negative association between changes in LVEF and ΔBNP after mitral annuloplasty.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, variations in LVEF and LVDs were used for cardiotoxicity evaluation (17)(18)(19). LVEF variation was measured by calculating maximum drop in LVEF (ΔLVEF), calculated using baseline LVEF-monitored minimum LVEF.…”
Section: Cardiotoxicity Evaluation Criteriamentioning
confidence: 99%